Are there gender differences in the association between body mass index and left ventricular diastolic function? A clinical observational study in the Japanese general population. Issue 11 (21st September 2020) - Hirokawa, Megumi; Daimon, Masao; Kozuma, Kayoko; Shinozaki, Tomohiro; Kimura, Koichi; Nakao, Tomoko; Nakanishi, Koki; Sawada, Naoko; Ishiwata, Jumpei; Yoshida, Yuriko; Kato, Tomoko S; Mizuno, Yoshiko; et al.
Abstract: Background: Increased body mass index (BMI) is a major risk factor for heart failure with preserved ejection fraction (HFpEF), and HFpEF is more prevalent in elderly females than males. We hypothesized that there may be gender differences in the association between BMI and echocardiographic left ventricular (LV) diastolic parameters. Methods: We enrolled 456 subjects (243 males) without overt cardiac diseases, all of whom underwent a health checkup. Early (E) and late (A) diastolic transmitral flow velocity, early diastolic mitral annular velocity (e′), and left atrial (LA) volume index were measured by echocardiography to assess LV diastolic function. To examine gender differences in the association between BMI and LV diastolic function, we analyzed the interaction effects of gender on the association between BMI and echocardiographic LV diastolic parameters. Results: Although there were significant gender differences in the association between BMI and E/A and e′ in the crude model (interaction effect 0.037 and 0.173, respectively; P = .006 and .022, respectively), these differences were not statistically significant after adjustment for factors related to LV diastolic function. On the other hand, there were significant associations between BMI and LV diastolic parameters in each gender, even after adjustment. Conclusions: Our findings suggest there is no gender difference in the association between BMI and echocardiographic LV diastolic parameters. However, the association between BMI and LV diastolic parameters was significant in both genders. Controlling body weight might be beneficial for both women and men to prevent progression of LV diastolic dysfunction and development of HFpEF.